2014
DOI: 10.1002/ppul.23142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of tracheal cobblestoning in children

Abstract: The prevalence of tracheal cobblestones in otherwise healthy children is high and is not associated with GERD or respiratory infection. The gender and age related differences are novel interesting findings that require further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A previous study of preoperative bronchofibroscopy in children reported the incidence of tracheobronchial cobblestone mucosa to be 38.8%; the incidence in children under 3 years of age (43.5%) was significantly lower than that of children over 3 years of age (56.4%) and cobblestone mucosa was not detected in infants younger than 4 months of age. 3 The different incidences across different age groups are most likely to be associated with maturity of the immune system. We believe that this is the first report of this type of lesion in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study of preoperative bronchofibroscopy in children reported the incidence of tracheobronchial cobblestone mucosa to be 38.8%; the incidence in children under 3 years of age (43.5%) was significantly lower than that of children over 3 years of age (56.4%) and cobblestone mucosa was not detected in infants younger than 4 months of age. 3 The different incidences across different age groups are most likely to be associated with maturity of the immune system. We believe that this is the first report of this type of lesion in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has failed to confirm this assumption. 3,4 The pathogenesis of tracheobronchial cobblestone mucosa in utero is still unclear, partly because the fetal airway fills with lung fluid. It is difficult for stimulants to enter the airway unless hypoxia causes gasping breathing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common finding in bronchoscopic airway evaluations is a “cobblestone” appearance of the airway, which is often attributed to GERD or aspiration. Dave et al reported a large retrospective study of healthy children who had rigid tracheoscopy at intubation for elective surgical procedures, and found evidence of cobblestoning in almost 40%, but with no association between prevalence of cobblestones and GERD, current or recent respiratory infection, or concomitant enlarged tonsils.…”
Section: Diagnostic Testing/endoscopymentioning
confidence: 99%